Answer:
the answer is x=33 so it's 4(33)+5=137
Hello,
f^(-1)(f(x))=f^(-1)(1/2 * x)=2*(1/2 * x)=(2*1/2)*x=1*x=x
f(f^(-1)(x))=f(2x)=1/2* (2x)=(1/2*2)*x=1*x=x
Answer:yo momma
Step-by-step explanation:
(1) x represents the number of apples bought, y represents the number of bananas.
(2) each term represents the total costs of a given fruit, so 0.50x is the total cost of apples and 0.30y is total cost of bananas.
(3) The coefficients are unit prices: coefficient 0.50 is the price of 1 apple, 0.30 is the price of 1 banana.